Distribution of rotavirus genotypes in the postvaccine introduction era in Ashaiman, Greater Accra Region, Ghana, 2014‐2016. Issue 11 (23rd July 2019) - Letsa, Victor; Damanka, Susan; Dennis, Francis; Lartey, Belinda; Armah, George E.; Betrapally, Naga; Gautam, Rashi; Esona, Mathew D.; Bowen, Michael D.; Quaye, Osbourne
Abstract: Group A Rotaviruses (RVAs) are the most important etiological agents of acute gastroenteritis (AGE) in children less than 5 years of age. Mortality resulting from RVA gastroenteritis is higher in developing countries than in developed ones, causing a huge public health burden in global regions like Africa and South‐East Asia. This study reports RVA genotypes detected in Ashaiman, Greater Accra Region, Ghana, in the postvaccine introduction era for the period 2014‐2016. Stool samples were collected from children less than 5 years of age who visited Ashaiman Polyclinic with AGE from November 2014 to May 2015 and from December 2015 to June 2016. The samples were tested by enzyme immunoassay (EIA), and one‐step multiplex reverse transcription polymerase chain reaction was performed on the EIA positive samples for gel‐based binomial genotyping. Of the 369 stool samples collected from children with AGE, 145 (39%) tested positive by EIA. Five VP7 (G1, G3, G9, G10, and G12) and three VP4 (P[4], P[6] and P[8]) genotypes were detected. Eight G/P combinations were identified of which, G3P[6], G12P[8], G1P[8], and G9P[4] were the most prevalent and responsible for 93 (68%) of the AGE cases, and seven mixed‐types were detected which represented 8% of the RVA cases. High prevalence, diversity, and mixed‐types of RVAs were detected from Ashaiman with the emergence of unusual genotypes. Highlight: High prevalence, diversity, mixed infections, and rare group A rotaviruses were found in Ashaiman, Accra‐Ghana in the postrotavirus vaccine introduction era.